Outcome of Surgery in Ruptured Aneurysm: A Study of 48 Cases - Haradhan Deb Nath; Razib, KH Olinur; Rathin Halder; Md Ataur Rahman; Md Motasimul Hasan; Abu Naim Wakil Uddin; Md Rabiul Karim; Sudip Barua; SK Farhad Munir; Barua, Kanak Kanti (Bangladesh Journal of Neurosurgery, 2024)
Background : Rupture aneurysm is a dangerous clinical condition of a patient. The aim of this study is to find out the outcome of rupture aneurysm after microsurgical clipping. Method: This was a prospective cross sectional study and was conducted at the department of Neurosurgery, Bangabandhu Sheikh Mujib Medical University, Dhaka from January 2011 to April 2022. Results : Among 48 patient 30(62.5%) were male. It was documented that 32(66.6%) patients were belong to 51-60 years. It was evident that the most of the clinical presentation was history of sudden severe headache 48(100%), 32(66.6%) patients had presented with vomiting and brief loss of consciousness had 24(50%). The highest percentage of WFNS grading of during admission were (1-3), 32(66.6%). Peroperative rupture during surgery were 16(33.33%). During discharge good recovery was occurred 38(79.7%) and 5(10.5%) had death. Conclusion: We have treated all the case by microsurgical clipping. Still microsurgical clipping is one of the gold standard procedure for rupture intracerebral aneurysm. Bang. J Neurosurgery 2023; 12(2): 114-121